2017
DOI: 10.1016/j.jaac.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost Offset Associated With Early Start Denver Model for Children With Autism

Abstract: Early Characteristics of Autism; http://clinicaltrials.gov/; NCT0009415.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 33 publications
2
93
0
1
Order By: Relevance
“…Moreover, screening algorithms derived from machine learning (thus, sample dependent) analyses need replication using hypotheses driven designs. The feasibility of implementation in the general community must also be established, with consideration of necessary training, acceptability to parents, and costs, although potential long term savings related to improved outcomes resulting from earlier diagnosis and treatment should be taken into account 8. Finally, because of the etiologic heterogeneity of the disorder some biomarkers may be specific to certain subtypes of ASD and informative for only a subset of cases 113.…”
Section: Potential Clinical Utility Of Predictive Biomarkers For Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, screening algorithms derived from machine learning (thus, sample dependent) analyses need replication using hypotheses driven designs. The feasibility of implementation in the general community must also be established, with consideration of necessary training, acceptability to parents, and costs, although potential long term savings related to improved outcomes resulting from earlier diagnosis and treatment should be taken into account 8. Finally, because of the etiologic heterogeneity of the disorder some biomarkers may be specific to certain subtypes of ASD and informative for only a subset of cases 113.…”
Section: Potential Clinical Utility Of Predictive Biomarkers For Asdmentioning
confidence: 99%
“…Cost effectiveness studies have modeled the potential long term functional benefits4 and savings56 associated with earlier access to interventions. In a two to three year follow-up of a clinical trial,7 toddlers who had received early intensive treatment not only experienced functional gains but also needed fewer services than those who received “treatment as usual,” resulting in overall cost savings 8. Thus, early intervention—and by extension, early diagnosis—have the potential to improve function and reduce societal costs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (e.g., Refs. [13][14][15][16][17] have related improved clinical outcomes to early intervention, providing motivation for diagnosing individuals as early as accurate diagnosis is possible.…”
mentioning
confidence: 99%
“…Recent research from other fields has shown that high-quality early learning programs for disadvantaged children can deliver a high return on investment, with positive long-term benefits across educational, health, social, and employment outcomes (García et al, 2017). Preliminary evidence suggests that high-quality ASD early interventions may hold the same potential (Cidav et al, 2017).…”
mentioning
confidence: 99%